Testing the Relationship between Stock Prices of Cross Listed Firms: A Case of Standard Chartered PLC** - Mahadevan, Sriram (Journal of Contemporary Research in Management (JCRM), 2015)
The present study has empirically investigated long term relationship between Indian Depository Receipt (IDR) and the respective underlying share price of the only IDR issue of Standard Chartered PLC in India. The study has used the daily closing prices of the bank in India {STAN (NSE)} and prices in U.K {STAN (LSE)} from 30-6-2011 to 30-6-2014. The result shows that IDR and its underlying shares are stationary at first difference and not normally distributed. There is no long term relationship between IDR and the underlying share price of Standard Chartered PLC. VAR results indicate that the performance of the bank’s share price depends upon the lagged values in the respective markets. Additionally, impulse response function reveals that there is significant and higher response to the shock of STAN (NSE) to STAN (NSE) and significant and higher response of STAN (LSE) to the shock of STAN (NSE) when compared to its own values. The major conclusion of the study is that price discovery happens in the respective markets and investors’ can study their respective markets for appropriate strategies. Keywords- Indian Depository Receipt, VAR, impulse response function, Standard Chartered PLC, Stationarity JEL Classification Code- G15, F36 Paper type- Empirical